Mikroformų ilgaamžiškumo problemos (Knygotyra, 2026)
According to the situation at present the problem of longevity of microforms (microfilms, microfiches, microcards) is still in the experimental stage, but despite this we are sure that microfilms and microfiches already compete with the longevity of paper as the durability of archival material is concerned.In future, employing all means of special durable material made for archival keeping of microforms, microforms on the transparent bases will preserve longer than even the best sorts of paper we have at present.Great prospects are foreseen for holograms as far as archival keeping of information is concerned. Microfiches and holograms will take advantage in all micrographic systems, simple ones and those used in electronic computers. Videomagnetic carriers will help to use the information accumulated in electronic computers and other information systems. At the same time besides the archival function of microprint the function of cheap spreading of information which is one of the main advantages of microprint will be displayed. The archival keeping of material on microforms will remain of paramount importance even then when part of printing will be done on special paper for durable keeping of information.